1991
DOI: 10.1177/00220345910700070401
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Degradation of Mucin by Streptococcus oralis and Streptococcus sanguis in Mixed Chemostat Cultures

Abstract: Oral streptococci can grow in mucin by utilizing the oligosaccharide chains as a source of carbohydrate. The degradation of the oligosaccharides by these species is accomplished by exoglycosidase activities. In this experiment, it was investigated whether strains from different species could cooperate in the release of sugars from the mucin oligosaccharide. To this end, Streptococcus sanguis Ny 584 and Streptococcus oralis strain Ny 586 were grown continuously in a chemically-defined medium, with pig gastric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 25 publications
3
36
2
Order By: Relevance
“…This change was seen for strains of S. sanguis but not S. oralis (Nieuw Amerongen et al, 1992). Another study has reported that those two species may collaborate in breaking down mucin oligosaccharides (Van der Hoeven and Camp, 1991). This illustrates the combined importance of both protein and bacterial polymorphism.…”
Section: (C) Protein Polymorphismsmentioning
confidence: 87%
See 1 more Smart Citation
“…This change was seen for strains of S. sanguis but not S. oralis (Nieuw Amerongen et al, 1992). Another study has reported that those two species may collaborate in breaking down mucin oligosaccharides (Van der Hoeven and Camp, 1991). This illustrates the combined importance of both protein and bacterial polymorphism.…”
Section: (C) Protein Polymorphismsmentioning
confidence: 87%
“…It seems mainly to be involved in tissue coating (Tabak, 1995), but the protein backbone recently has been observed to bind Hemophilus paminfluenzae (Veerman et al, 1995). Mucin oligosaccharide side-chains likewise may provide a nutritional substrate for common streptococcal species (Van der Hoeven and Camp, 1991). MG2 has a molecular weight of 125,000, and its side-chains may participate in both the aggregation and adherence of oral streptococci (Tabak, 1995).…”
Section: (Ii) Salivary Proteins-microbial Interactionsmentioning
confidence: 99%
“…The idea that different bacterial species possess individual enzymatic activities that act in succession was explore in experiments using hog gastric mucin as the sole source of carbohydrate for growth and synergistic degradation of mucin was observed by van der Hoeven and Camp [9]. These investigators reported that Streptococcus sanguis (S. sanguis) Ny 584 reached significantly higher cell densities in mixed chemostat cultures with Streptococcus oralis (S. oralis) Ny 586 than in pure culture [9], supporting the hypothesis that complementary enzymatic activities from each species coordinate their actions to increase the efficient use of this mucin.…”
Section: Cellular Growth On Saliva As Sole Nutritional Sourcementioning
confidence: 99%
“…Compared to many ecosystems, the nutrient supply available to bacteria in the oral cavity is more abundant and localized at times when the host consumes food (feast), although the period of time over which this occurs is much shorter than when no added nutrients are consumed (famine) (Carlsson & Johansson, 1973;De Jong & Van der Hoeven, 1987;Van der Hoeven & Camp, 1991). In other micro-environments of the oral cavity, such as root canals of teeth, nutrients are commonly scarce and the colonizing micro-organisms frequently need to survive under nutrient deprivation.…”
Section: Introductionmentioning
confidence: 99%